Stress, coping, coping effectiveness and emotions in Malaysian Elite tenpin bowlers: Role of context and importance - Wong, R.S.K.; Teo, E.W.; Polman, R.C.J. (Taylor & Francis, 2015)
Professional tenpin bowlers were examined for their stressors experienced, coping, coping effectiveness and emotional reactions prior to and during minor and major competitions. Fifteen tenpin bowlers (male n = 6; female n = 9) completed a diary pack on three separate periods: one minor competition period and two major competitions periods. Tenpin bowlers completed a diary to report their stressor encounters, coping strategies, coping effectiveness, resulting emotions and their intensity on a daily basis. Results showed that the tenpin bowlers experienced a limited (n = 5) number of stressors over time which accounted for 95% of the stressors reported, almost similar to those observed in Caucasian athletes. However, unlike Caucasian athletes our sample reported a similar number of positive and negative emotions. Context (training vs. competitions) and the importance of the competition were found to influence stress and coping process especially at the level of individual stressors. Findings suggest a need to further examine cultural similarities and differences in the stress, coping and emotion process among athletes to prevent misunderstanding and miscommunication. This will allow the development interventions which are not only situation and context specific but also culturally sensitive.